Comparison between UV-spectrophotometry and HPLC methods to determine napropamide concentration in soil sorption experiment. - Sadegh-Zadeh, Fardin; Abd. Wahid, Samsuri; Omar, Dzolkhifli; Othman, Radziah; Seh-Bardan , B.J.; Sajudi, N.A. (2011)
In this study we compared the High Performance Liquid Chromatography (HPLC-UV) and the Ultraviolet (UV) spectrophotometry methods for measuring the herbicide napropamide concentrations in soil solution during batch equilibrium sorption study. Experiments were conducted to compare the calibration curves, recovery in background solution and spiked soil samples, intra and inter day precision and mass balance of the two methods. Mass balance of napropamide in the sorption study was determined from the difference between the initial napropamide content in the supernatant and the equilibrium concentration. Although DOC interfered with UV wave absorption by napropamide in the UV-spectrophotometry method, it was easily corrected by using a blank solution containing the same amount and type of DOC as used in the sample. The intra and inter day precision experiments indicated the measured napropamide concentrations using both methods were equally reproducible and consistent. The recovery of napropamide from spiked soil samples decreased with increasing amount of clay and organic matter but recoveries for both methods exceeded 88% and the recovery of the UV-spectrophotometry method was comparable to the HPLC. The measured concentrations of napropamide in soil solution supernatant used for the sorption study showed no significant differences between the two methods. We found that the UV-spectrophotometry method was reliable to determine the concentration of napropamide in the supernatant of the soil solution used in the sorption study. Therefore, the UV-spectrophotometry method can be used as an alternative method to HPLC for determination of napropamide concentration in soil batch equilibrium sorption study.